Assessment of the acute toxicity of agrochemicals on earthworm (Aporrectodea caliginosa) using filter paper contact and soil mixing tests (Asian Journal of Agriculture, 2023)
Abstract. El-Aswad AF, Fouad MR, Aly MI. 2023. Assessment of the acute toxicity of agrochemicals on earthworm (Aporrectodea caliginosa) using filter paper contact and soil mixing tests. Asian J Agric 7: 14-19. Earthworms are suitable bioindicators of chemical contamination in terrestrial ecosystems. Therefore, adult earthworms (Aporrectodea caliginosa Savigny, 1826), which are common in Egyptian rice fields were used to study the side effects of fenitrothion and thiobencarb. Also, it was used two common Egyptian soil types; alluvial soil (clay soil) and the calcareous soil (sandy clay loam soil). Two tests were used; filter paper contact test at 24, 48 and 72 h, and the soil mixing test at 5 and 10 days. The effect of both pesticides on mortality of earthworm was insignificant at 24 h with a low mortality percentage. LC50 value of fenitrothion and thiobencarb were 83.16, 288.26, 24.67, and 39.98 µg a.i mL-1 at 48 and 72 h, respectively. Based on the LC50 values, fenitrothion was 3.5 and 1.6 times more toxic than thiobencarb at 48 and 72 h, respectively. At 5 and 10 days after treatment, respectively, the LC50 for fenitrothion in the soil mixing test decreased from 334.27 to 55.45 in clay soil and from (415.90) to (25.00) in sandy soil. Regarding to fenitrothion in soil mixing test, the LC50 was reduced from 334.27 to 55.45 in clay soil and from 415.90 to 25.00 in sandy soil at 5 and 10 days after treatment, respectively. Also, the LC50 of thiobencarb in clay soil was decreased from 0.93 to 0.41 and from 55.28 to 10.65 at 5 and 10 days, respectively. In general, a positive relation was recorded between the tested pesticide toxicity on earthworm and concentrations, and also exposure time. Fenitrothion was more toxic on earthworm in contact filter paper test than thiobencarb. While, in clay soil, fenitrothion was least toxic to the earthworm in soil mixing test, this could be attributed to the slow degradation in the worms and subsequently less elimination of the metabolites as well as attributed to its higher adsorption and lower desorption in soil.
Keywords: Earthworm, fenitrothion, soil, thiobencarb